Niobium Doping in BiVO4: Interplay Between Effective Mass, Stability, and Pressure. Issue 5 (1st February 2019) - Sarker, Hori Pada; Rao, Pratap M.; Huda, Muhammad N.
Abstract: We have applied density functional theory to study the electronic structure changes caused by Nb incorporation in BiVO4 and the application of external pressure. The overall solubility of Nb in BiVO4 is usually high, and the presence of oxygen vacancies affect the dopability of Nb in BiVO4 . Through the analyses of the chemical‐potential landscape, we have determined the single‐phase stability zone of BiVO4 with the Nb doping. The most favorable Nb doping is simultaneous substitutions at both V‐ and Bi‐sites. Even though Nb substitution at only V‐site is next favorable, the band gap change is not very significant which agrees with an earlier experiment. However, it does change the electron effective mass by 20 % owing to the presence of Nb 4d bands in the conduction bands, which explains better catalytic activity by Nb‐doped BiVO4 . In addition, application of external pressure the single‐phase stability zone in the chemical‐potential landscape. We have also focused on the local structural distortions near the Nb doping site, especially on the BiO8 octahedra. We have shown here that pressure‐induced symmetrization of BiO8 dodecahedron lowers the electron's effective mass further and therefore can help to improve the photoconduction property of BiVO4 . Abstract : Under pressure : DFT was applied to study the electronic structure changes of BiVO4 due to Nb doping. We have calculated the solubility of Nb doping, and the solubility was high. Single‐phase stability zone of BiVO4 has also been calculated within the chemical potential landscape. Furthermore, applying external pressure was found to enhance the solubility of Nb and electron conductivity of Nb doped BiVO4 .